Pengaruh Beban Pajak, Bonus Plan, dan Tunneling Incentive Terhadap Keputusan Transfer Pricing - Gita Cahyani; Muhammad Riza Hafizi; Wehdawati Wehdawati (Journal of Business and Economics Research (JBE), 2023)
Transfer pricing is indicated as a strategic step in conducting transactions regarding competitive pricing by related companies. With transfer pricing, the company can assess the performance of the members or divisions of the company. The transfer pricing problem arises because of the manipulation by the company. This study aims to determine the influence of the tax load, bonus plan, and tunneling incentive partially and simultaneously on the transfer pricing decision. The research used a quantitative method with the expost facto design. The population in this study was companies that were members of the Jakarta Islamic Index (JII) in 2018-2020. The research sample was selected using purposive sampling of 11 companies from 30 companies. This study used secondary data obtained from the Indonesia Stock Exchange. The data analysis technique used was multiple linear regression analysis with SPSS 26 program. The results showed that the f test of the tax load, bonus plan, and tunneling incentive simultaneously had a significant effect on the transfer pricing decision. Meanwhile, the results of the t-test showed that the tax load did not affect the transfer pricing decision. The bonus plan had a significant negative effect on the transfer pricing decision. The tunneling incentive had a significant positive effect on the transfer pricing decision.